Traceability and product recall of halal products - Zurina Shafii; Siti Zamanira Mat Zaib; Azila Jaini; Suraya Mahmood (2014)
This paper aims to investigate the role of traceability system during product recall and the measures of traceability adopted by the selected company to trace the product. This study also attempts to investigate the impacts of product recall to the producers and the methods used by the company to recover negative impacts and reputations. The finding showed that the company uses seven measures to improve Halal compliance management for the purpose to recover costs and loss of customers’ confidence. There are significant effects to the company when recalling their product from the market place especially on the manufacturer’s image and profitability. The Company faces challenges in recovering loss when there are product recalls. Hence, the Company initiates methods to regain consumer’s confidence as well as product distributors.